Chad : Second Review of the Program Under the Extended Credit Facility, Request for Waivers of Nonobservance of Performance Criteria, And Financing Assurances Review-Press Release; Staff Report; and Statement by the Executive Director for Chad. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2018)
This paper discusses Chad's Second Review of the Program Under the Extended Credit Facility, Request for Waivers of Nonobservance of Performance Criteria (PCs), and Financing Assurances Review. All but one PC for end-December 2017 were met, as were all structural benchmarks Most indicative targets for end-March 2018 were also met. The continuous PC on the nonaccumulation of external arrears was missed. The authorities are requesting waivers for the two missed PCs. The final agreement to restructure the Glencore debt was signed in June (prior action); it is in line with the program and will restore debt sustainability and generate sufficient financing for the program.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet